Moradias sobredimensionadas dos anos 70‐90 na periferia de Braga: processo de transformação - Loureiro, Francisco Michael Oliveira (2015)
According to the latest census (2011) covering the Portuguese housing stock, there is a considerable number of sub-occupied buildings and most of them were built before the first Portuguese Thermal Code (RCCTE). In view of the objectives of the European Union (20-20-20), it is necessary to contribute to the rehabilitation of existing buildings by promoting the densification of oversized houses, while complying with up-to-date comfort standards and codes.Â In this sense, this research is aimed to analyse this problem at the outskirts of Braga, by identifying the type-morphology of oversized buildings, assessing the degree of satisfaction and expectations of both owners and inhabitants and developing and testing a systematic design tool.Â Through the development of an intervention kit, wich systematizes and priorizes design strategies and solutions, the design team can have the necessary decision-making support tool to improve the spacial design of the building whilst considering energy efficency, sustainability and improvemente of interior environmental quality.